1995
DOI: 10.1002/lipi.19950970104
|View full text |Cite
|
Sign up to set email alerts
|

Changes of Tocopherols and Phospholipids during Heating of Low‐Erucic Rapeseed Oil at Temperature Similar to Fritting

Abstract: 0.02 M . B u c h o w s k i , Malgorzata N o g a l a -K a l u c k a a n d M . G o g o l e w s k i *Rapeseed oilcrude and refinedand the fraction of acylglycerols isolated from these oils were added to natural amounts of tocopherols or phospholipids and were heated in conditions similar to fritting during 30 hours. Maximum formation of dimers amounted to 24% of initial quantity of tocopherols. In the samples heated at 170°C dimers occurred incidentally, only in model systems of acylglycerols with addition of toc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

1998
1998
2010
2010

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 7 publications
0
6
0
Order By: Relevance
“…The formation of new compounds at high temperatures has been studied in model systems (Fujitano and Ando, 1977;Verleyen et al, 2001aVerleyen et al, 2001b and in refined oils (Buchowski et al, 1995;Murkovic et al, 1997;Rennick and Warner, 2006). It has been reported that tocopherols have a very low volatility at frying temperature (Pongracz, 1988) and hence, their rapid loss is due to their degradation.…”
Section: Other Natural Antioxidantsmentioning
confidence: 99%
“…The formation of new compounds at high temperatures has been studied in model systems (Fujitano and Ando, 1977;Verleyen et al, 2001aVerleyen et al, 2001b and in refined oils (Buchowski et al, 1995;Murkovic et al, 1997;Rennick and Warner, 2006). It has been reported that tocopherols have a very low volatility at frying temperature (Pongracz, 1988) and hence, their rapid loss is due to their degradation.…”
Section: Other Natural Antioxidantsmentioning
confidence: 99%
“…of the same oil, fat decomposition products gradually increase and its sensorial characteristics change [6,9].…”
Section: Quality Changes In Edible Oils At High Temperature Kinetic mentioning
confidence: 99%
“…turn to a linear relationship of 0w and further into subsequent orders of the dw type [9]. turn to a linear relationship of 0w and further into subsequent orders of the dw type [9].…”
Section: Analysis Of Peroxide Numbermentioning
confidence: 99%
“…In our paper we have specified a method for determining the increase of the peroxide number rate and the decrease of the savoriness rate with respect to the oils under consideration; in addition the methods for comparing the rates for changing quality parameters have been studied. of the same oil, fat decomposition products gradually increase and its sensorial characteristics change [6,9].…”
Section: Quality Changes In Edible Oils At High Temperature Kinetic mentioning
confidence: 99%